CHARACTERIZATION OF AGRICULTURAL LAND USING SEISMIC REFRACTION TOMOGRAPHY AND ELECTRICAL RESISTIVITY TOMOGRAPHY - Nabil Pijati, Naufal
Cilembu sweet potato, a primary agricultural product of Cilembu Village, exhibits significant economic potential. This is evident in the consistently increasing market demand for this commodity. However, productivity fluctuations due to factors such as weather, rainfall, seed quality, cultivation practices, and soil degradation hinder efforts to meet market demands. Geophysical methods, renowned for their non-destructive nature, have been extensively employed in characterizing soil structures. This study utilizes Seismic Refraction Tomography (SRT) and Electrical Resistivity Tomography (ERT) to investigate soil properties. The resulting Vp and resistivity models reveal distinct soil layer responses to seismic and electrical signals, enabling identification of soil horizons. Horizon A, characterized by Vp values ranging from 200 to 400 m/s and resistivity values between 800 and 1000 ?m, is determined to exist at depths of 0-100 cm. Horizon B exhibits Vp values of 400-600 m/s and resistivity values of 400-800 ?m. Model validation was conducted through test pit at multiple sites within the study area.